Open Access Publishing - Hadfield, Amelia (2013)
The rise of open source online journals, free online courses, and other changes in the research and education environment, coined the "academic spring" by some commentators, represents an increasing trend in opening up the rules of access for research. Universities, libraries, publishers and even governments are paying attention to this new movement often referred to with the acronym A2K (access to knowledge).